2020
DOI: 10.1055/a-1328-5093
|View full text |Cite
|
Sign up to set email alerts
|

The N-Methyl-(2S, 4R)-trans-4-hydroxy-L-proline-Enriched Methanol Fraction from Sideroxylon obtusifolium Shows an Anticonvulsant Activity Associated with its Anti-inflammatory/Antioxidant Actions

Abstract: Epilepsy is a neurological disorder characterized by recurrent seizures, resulting from excessive neuronal discharges. Sideroxylon obtusifolium is used in Brazil for its anti-inflammatory/antioxidant properties, known to be involved with epilepsy. The anticonvulsant effects of the methanol fraction from S. obtusifolium leaves, rich in N-methyl-(2S,4R)-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In another study by de Aquino et al, 10% Methyl-(2R, 4R)-trans-4-hydroxy-L-proline gel was formulated and used to treat wounds induced on mice. It was observed that while collagen deposition increased on days 7 and 12, only 58% wound reduction was observed by day 12 suggesting that the effect of hydroxy-L-proline in enhancing wound contraction may not be as pronounced as that of lysine in this current study [40]. Collagen is also known to increase the tensile strength of the tissue during healing at the wound area [39].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In another study by de Aquino et al, 10% Methyl-(2R, 4R)-trans-4-hydroxy-L-proline gel was formulated and used to treat wounds induced on mice. It was observed that while collagen deposition increased on days 7 and 12, only 58% wound reduction was observed by day 12 suggesting that the effect of hydroxy-L-proline in enhancing wound contraction may not be as pronounced as that of lysine in this current study [40]. Collagen is also known to increase the tensile strength of the tissue during healing at the wound area [39].…”
Section: Discussionmentioning
confidence: 57%
“…The number of microvessels in the granulation tissue and the thickness of the central region of the epidermis to dermis indicate the depth of structural wound healing taking place as formation of microvessels is necessary for vascular function at the wound site. Formulations F1-F3 showed higher numbers of microvessels and more thickness of the central region of the epidermis and the dermis compared to the control [40][41][42].…”
Section: Discussionmentioning
confidence: 90%
“…The previously reported effects of this compound include anti-oxidant, anti-inflammatory, anti-nociceptive, as well as hypoglycemic activity [15]. In addition, the anti-convulsing effects of the L-proline derivative were evaluated in different models of PTZ-and Piloinduced epilepsy in mice models [16]. Furthermore, the nanoemulsion of Sideroxylon obtusifolium is used to treat schistosomiasis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Extracts and fractions enriched in N-methyl-(2S,4R)-trans-4-hydroxy-L-proline (NMP), a constituent of S. obtusifolium leaves, have demonstrated biological activities as antioxidants (Aquino et al 2020) and systemic anti-inflammatories (Aquino et al 2017(Aquino et al , 2019(Aquino et al , 2020. NMP is a derivative of L-proline, an amino acid commonly used as a dietary supplement to stimulate collagen synthesis in the body (Vitagliano et al 2001).…”
Section: Introductionmentioning
confidence: 99%